The collaborative habit life lessons for working together - Tharp, Twyla 1941- (Simon & Schuster, 2009)
In a career that has spanned four decades, choreographer Twyla Tharp has collaborated with great musicians, designers, thousands of dancers, and almost a hundred companies. She's experienced the thrill of shared achievement and has seen what happens when group efforts fizzle. Her professional life has been--and continues to be--one collaboration after another. In this practical sequel to her Creative Habit, Tharp explains why collaboration is important to her, and can be for you. She shows how to recognize good candidates for partnership and how to build one successfully, and analyzes dysfunctional collaborations. Tharp sees collaboration as a daily practice, and her book is rich in examples from her career--and she suggests that the lessons you learn by working together professionally can help you in your personal relationships.--From publisher description